Post-consumer glass packaging in the selective collection system: a case study of the city of Londrina - Aligleri, Lilian; Aligleri, Luiz Antonio; Gois, Gabriela Lino (Revista de Administração da UFSM, 2020)
Purpose: This article presentes the results of an in-depth and contextualized study on the problems in the commercialization of glass containers sent to the selective collection system of the city of Londrina-PR, Brazil. Design: The methodological strategy was the triangulation of sources of evidence desiring to understand the situational characteristics, as well as the operational and environmental challenges faced by the local actors involved, especially the cooperatives. Quantitative and qualitative study case using primary and secondary data collection from multistakeholders. Findings: The data collected here allow us to conclude that vitreous materials have demonstrated difficult commercialization processes and are among those materials that are economically less interesting for cooperatives, intensifying the high social fragility of cooperates. Practical implications: The search for solutions to environmental and economic problems caused by the high generation of municipal solid waste in Brazil still have strong deficiencies in methodologies and technologies. Social implications: How the reverse logistics of vitreous packaging is operationalized has increased public financing with this type of material, since the sales price obtained by waste pickers does not corroborate the economic support of cooperative enterprises. Originality/value: This study allows to advance in the explanation and description of the way of structuring the reverse chain of vitreous packaging, especially in medium-sized municipalities in the inland. Keywords: post-consumption; packaging; glass; recycling; selective collection